2005
DOI: 10.1016/j.jconhyd.2005.05.006
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of hydrogeochemical processes on zero-valent iron reactive barrier performance: A field investigation

Abstract: Geochemical and mineralogical changes were evaluated at a field Fe0-PRB at the Oak Ridge Y-12 site concerning operation performance during the treatment of U in high NO3- groundwater. In the 5-year study period, the Fe0 remained reactive as shown in pore-water monitoring data, where increases in pH and the removal of certain ionic species persisted. However, coring revealed varying degrees of cementation. After 3.8-year treatment, porosity reduction of up to 41.7% was obtained from mineralogical analysis on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…The goal is to have contaminant levels below target concentration at compliance points down gradient of the barrier. The barriers also prevent groundwater contaminants from migrating to uncontaminated aquifers, which may be difficult to locate and remedy [87][88][89][90][91][92].…”
Section: Principles and Conceptmentioning
confidence: 99%
“…The goal is to have contaminant levels below target concentration at compliance points down gradient of the barrier. The barriers also prevent groundwater contaminants from migrating to uncontaminated aquifers, which may be difficult to locate and remedy [87][88][89][90][91][92].…”
Section: Principles and Conceptmentioning
confidence: 99%
“…iron oxides or calcite) on the electrical responses. Yet PRB precipitate mineralogy is normally complex, being dependent on the groundwater chemistry at the site, in many cases including both iron oxides and calcite (Furukawa et al, 2002;Morrison et al, 2002;Liang et al, 2003;Phillips et al, 2003;Liang et al, 2005 and electronic (iron metal) conductors causing decreases in electrical conduction and polarization and, presumably, in surface reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Zero valent iron (Fe 0 , ZVI) has been placed in permeable reactive barriers (PRB's) and injected into aquifers in order to effect aquifer remediation since the 1970s (e.g., [6][7][8][9][10]70,71,[93][94][95][96][97][98]). The principle historical remediation focus has been on the removal of organo-chlorides, organo-nitrates, phosphates, nitrates, arsenic and heavy metals (e.g., [26,70,71,93,94,[99][100][101][102]).…”
Section: E4 Loss Of Reactivity With Timementioning
confidence: 99%
“…Desalination associated with zero valent iron (ZVI, Fe 0 ) has been demonstrated in more than 160 batch trials (utilizing 0.2-240 L/batch [1][2][3][4][5]) and by monitoring the salinity of water flowing through granular Fe 0 permeable reactive barriers (PRB) [6][7][8][9][10]. These trials have demonstrated that ZVI desalination has potential applications for groundwater management, road runoff water management, agricultural water management, municipal and domestic water, emergency and disaster water requirements, feed and waste water treatment associated with conventional desalination plants, waste water associated with the extractive industries and environmental damage mitigation [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation